I CAN EXPLAIN IT: BLEACHING THROUGH FASHION AND UTTERANCES BY CELEBRITIES THAT MAKE CLARIFICATION - Fauzia Silma, Nailun Nahari; Rani, Selma Mutia; Rahmah, Fatiha; Umam, Robith Khoiril (KOMUNIKOLOGI: Jurnal Ilmiah Ilmu Komunikasi, 2024)
Celebrities are figures who get exposure in their lives. So when they make a mistake or something that tends not to meet the expectations of society, it will have an impact on their popularity and good name. To improve their image, celebrities use clarification to the public with a press conference. In the clarification, there are implicit aspects that are used to cover up the shortcomings of their mistakes. This research seeks to prove the use of clarification strategies in verbal aspects that play a role in supporting what celebrities say. As well as the use of bleaching, to create a religious image of celebrities to tend to cover up mistakes with visual aspects that they want to emphasize in order to create a holy impression for the viewer. This article analyzes two celebrity press conferences under the hook and qualitative research.  The findings reveal that Lexical Substitution, Elaboration of Information and Rearrangement of statement are used as a clarification strategy and bleaching through their fashion and verbal is existent. This study implies that clarification strategy and bleaching might apply on tendentious conversation not only on celebrities' clarification pers conference, but also fashion or gestures aspect that contain bleaching when required to hide a negative ambiance from them. Keywords: celebrities, clarification, utterances, bleaching, press-conference